Chemical Components and Antibacterial Activity of Cinnamomum culilaban Extract from Southeast Maluku - Kapelle, Imanuel Berly Delvis; Shielda Natalia Joris; Fauzan Saleh; Nini Munirah Renur (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
The bark of Cinnamomum culilaban, endemic to Southeast Maluku, has the potential as an antibacterial. This study aimed to determine the antibacterial activity of C. culilaban bark extract isolated using distillation and maceration methods and to determine the chemical components contained therein. Qualitative tests using GCMS and antibacterial activity testing against E. coli and S. aureus bacteria. The extraction results using the distillation method obtained a sedimentation of 3.28% and the maceration method of 28.03%. The chemical components of the distillation extract showed four main components: Eucalyptol 4.02%, (+)-2-Bornanon 2.32%, terpineol 1.49% and Safrole 86.78%. The chemical components of the maceration extract have five main components, namely (+)-2-Bornanon 1.35%, Terpineol 1.43%, Safrole 89.06%, Spathulenol 1.26%, and Methoxyeugenol 1.73%. The antibacterial activity of the distillation extract against E. coli bacteria is classified as strong, with the highest inhibition zone size at a concentration of 60% (13.47 Â± 1.14 mm). In contrast, for S. aureus bacteria, there is no antibacterial activity. The antibacterial activity of the maceration extract against S. aureus bacteria is classified as strong with the inhibition zone size at a concentration of 100% (11.87 Â± 1.15 mm). In contrast, for E. coli bacteria, there is no antibacterial activity.